Investigation of amorphous-SiC thin film deposition by RF magnetron sputtering for optical applications - Chaussende, Didier; Tabouret, Vincent; Crisci, Alexandre; Morais, Magali; Coindeau, Stéphane; Berthomé, Gregory; Kollmuß, Manuel; Wellmann, Peter; Jomard, François; Pinault-Thaury, Marie Amandine; Lu, Yaoqin; Shi, Xiaodong; et al. (Materials Science in Semiconductor Processing, 2024)
Silicon carbide (SiC) is a rapidly emerging material for photonic applications, thanks to its exceptional optical properties. To be used as a waveguide, SiC thin films must be deposited directly on silica at low temperature. Amorphous SiC films were deposited by RF magnetron sputtering using a single source of high-purity polycrystalline SiC. A systematic study of the chemical, structural and optical properties of the films was carried out, using a combination of XRD, XPS, SIMS, spectroscopic ellipsometry, Raman spectroscopy and UV–Vis absorption spectroscopy. The aim was to link deposition conditions to film properties. By exploring a three-parameter space (RF power, substrate temperature, pressure), we have demonstrated that RF power is the main parameter which controls the entire deposition process and film properties. By simply adjusting the RF plasma power between 150 and 450 W, it is possible to adjust the refractive index at a wavelength of 1.5 μm in the range 2.50–2.75 and vary the bandgap from 2.5 to 1.7 eV. This is attributed to a slight variation in film composition, particularly in terms of Si/C ratio and C–C bond concentration.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Amorphous; Deposition process; Magnetron sputtering; Optical properties; Silicon carbide